Influence Academic Supervision and Leadership on Teacher Performance Through Work Motivation at The Faculty of Education Science and at Universidade Oriental Timor Lorosa’e - da Costa Brandão, Zeferino; dos S. Gonçalves, Agustinho; Aderita, Aderita (Siber International Journal of Education Technology (SIJET), 2024)
The purpose of this research are 1) To analyze and prove the influence of academic supervision on motivating the work of teachers at the Faculty of Educational Science and at the Eastern University of Timor Lorosa'e; 2)to analyze and prove the influence of leadership on teacher work motivation at the Faculty of Educational Science and at the Oriental University of Timor Lorosa’e; 3) To analyze and prove the influence of work motivation on the performance of teachers at the Faculty of Educational Science and at the Oriental University Timor Lorosa’e; 4) To analyze and prove the influence of academic supervision and leadership on teachers' performance through work motivation at the Faculty of Educational Science and at the Eastern University of Timor Lorosa'e. The population of this research totals 38 teachers. This research uses quantitative descriptive methodology. The data collection technique through observation, questionnaire and documentation. Test validity and reliability of each variable item for use as a research variable. The method used to analyse data is the path analysis and the help of the computer application SPSS version 21.0. The research result showed that: 1) There is a significant influence between academic supervision (X1) and work motivation (Y); 2) There is a positive and significant influence between leadership (X2) and work motivation (Y); 3) There is no significant influence between academic supervision (X1) and teacher performance (Z); 4) There is a significant influence between leadership (X2) and teacher performance (Z); 5) There is a positive and significant influence between work motivation (Y) and teacher performance (Z); 6) Work motivation (Y) does not act as a mediator for the relationship between academic supervision (X1) and teacher performance (Z); 7) Work motivation (Y) is a mediator for the relationship between leadership (X2) due to the teacher's performance (Z).